The role of educational disciplines in the formation of future teachers' self-reflection - Кравець, Л. М. (Pedagogy of Higher and Secondary Education, 2012)
Kravets L. M. The role of educational disciplines in the formation of future teachers' self-reflection. Pedagogical technologies, the use of which is performed on the basis of humanist approach to the university economics students’ personality formation, are considered in the article. The main problems of their nominal use in educational process are determined.